Editorial | Stop the Academic Bullying: Our Internal Reflections for a Fairer Peer Reviews [Hentikan Perundungan Akademik: Refleksi Internal untuk Penilaian Sejawat yang Lebih Adil] - Edwin Adrianta Surijah (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2021)
Academic bullying in peer reviews is a cultural problem. This Editorial Note is intended to identify the unhelpful comments/critiques and to highlight the impact of unprofessional peer reviews toward the well-being and career development of fellow researchers. We acknowledge that we are part of the problems, and the necessary steps are needed to break the chain of the academic bullying culture in peer reviews. New guidelines for editors and reviewers are part of the solutions to promote constructive comments, as well as stronger internal consolidation throughout the peer reviews process. Perundungan akademik dalam penilaian sejawat (peer review) adalah sebuah permasalahan kultur. Catatan Editorial ini bertujuan mengindentifikasi komentar atau kritik yang tidak membangun, serta menggarisbawahi dampak penilaian sejawat yang tidak profesional terhadap kesejahteraan dan pengembangan karir sesama peneliti. Kami menyadari bahwa kami merupakan bagian dari permasalahan ini, dan diperlukan langkah-langkah untuk memutus rantai kultur perundungan akademik dalam penilaian sejawat. Pedoman baru bagi editor dan mitra bestari merupakan bagian dari solusi untuk mendorong komentar yang konstruktif, serta konsolidasi internal yang lebih kuat dalam proses penilaian sejawat.